God and happiness in Epicurus - da Silva Carvalho, Adriano (2024)
This article aims to understand the meaning of the phrase: "Θεοὶ μὲν γὰρ εἰσίν" - “Surely the gods exist” in the context of the so-called letter about the happiness of Epicurus. And, to this purpose, it will question the relationship of this enunciate with the program of the "Blessed life" of the philosopher of Samos. Epicuro was presenting his declaration of faith: Θεοὶ εἰσίν? Probably not. But it is true that he used theological language when he presented his plan of happiness. Why did he do it? This is the question that this article will seek to answer.